2012
DOI: 10.4236/as.2012.35086
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration and water-use efficiency of irrigated colored cotton cultivar in semiarid regions

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The scheduling of irrigation at 1.25×ET c with a 40-cm SSDI recorded a significantly higher seed cotton yield in both 2016 and 2017 (Table 2). Azevedo et al [33] reported that irrigation with 120% of that crop evapotranspiration under sprinkler irrigation produced the maximum seed cotton yield. Moreover, Shruti and Aladakatti [34] determined a significantly higher seed-cotton yield (4024 kg ha -1 ) in drip irrigation at 1.0 × ET c .…”
Section: Seed Cotton Yields Under the Different Drip Irrigation Systemsmentioning
confidence: 99%
“…The scheduling of irrigation at 1.25×ET c with a 40-cm SSDI recorded a significantly higher seed cotton yield in both 2016 and 2017 (Table 2). Azevedo et al [33] reported that irrigation with 120% of that crop evapotranspiration under sprinkler irrigation produced the maximum seed cotton yield. Moreover, Shruti and Aladakatti [34] determined a significantly higher seed-cotton yield (4024 kg ha -1 ) in drip irrigation at 1.0 × ET c .…”
Section: Seed Cotton Yields Under the Different Drip Irrigation Systemsmentioning
confidence: 99%